Combining a gravitational search algorithm, particle swarm optimization, and fuzzy rules to improve the classification performance of a feed-forward neural network. (October 2019) - Huang, Mei-Ling; Chou, Yueh-Ching
Highlights: Particle swarm optimization (PSO) and a gravitational search algorithm (GSA) were used to optimize the weights and biases of a FNN. The chronic kidney disease (CKD) and mesothelioma (MES) disease datasets were used as research objects. Fuzzy rules were used to optimize the parameters of a GSA to improve the performance of classifiers. Abstract: Background and objective: A feed-forward neural network (FNN) is a type of artificial neural network that has been widely used in medical diagnosis, data mining, stock market analysis, and other fields. Many studies have used FNN to develop medical decision-making systems to assist doctors in clinical diagnosis. The aim of the learning process in FNN is to find the best combination of connection weights and biases to achieve the minimum error. However, in many cases, FNNs converge to the local optimum but not the global optimum. Using open disease datasets, the purpose of this study was to optimize the connection weights and biases of the FNN to minimize the error and improve the accuracy of disease diagnosis. Method: In this study, the chronic kidney disease (CKD) and mesothelioma (MES) disease datasets from the University of California Irvine (UCI) machine learning repository were used as research objects. This study applied the FNN to learn the features of each datum and used particle swarm optimization (PSO) and a gravitational search algorithm (GSA) to optimize the weights and biases of the FNN classifiers based on the algorithms inspired by the observation of natural phenomena. Moreover, fuzzy rules were used to optimize the parameters of the GSA to improve the performance of the algorithm in the classifier. Results: When applied to the CKD dataset, the accuracies of PSO and GSA were 99%. By using fuzzy rules to optimize the GSA parameter, the accuracy of fuzzy–GSA was 99.25%. The accuracies of the combined algorithms PSO–GSA and fuzzy–PSO–GSA reached 100%. In the MES disease dataset, all methods exhibited good performance with 100% accuracy. Conclusions: This study used PSO, GSA, fuzzy–GSA, PSO–GSA, and fuzzy–PSO–GSA on CKD and MES disease datasets to identify the disease, and the performance of different algorithms was explored. Compared with other methods in the literature, our proposed method achieved higher accuracy